"Mek some noise" : gospel music and the ethics of style in Trinidad - Rommen, Timothy (Music of the African diaspora, 2007)
Timothy Rommen presents an ethnographic study of Caribbean gospel music, engaging the musical world of contemporary Christians in Trinidad and Tobago at the nexus where music and religion meet.